(untitled) (Research, Society and Development, 2023)
Antimicrobials are drugs used to inhibit the growth of bacteria and fungi, thus, they are indicated for the treatment of microbial infections, but their excessive use can lead to the selection of resistant strains. On the other hand, Moringa oleifera is a plant whose parts are commonly used in traditional medicine, due to their anti-inflammatory and antibacterial potential. The aim of this study was to evaluate the antimicrobial potential of Moringa oleifera leaf extract against Staphylococcus aureus. Strains of Staphylococcus aureus isolated from clinical samples were maintained in nutrient agar, resuspended in sterile saline solution and streaked onto the surface of Müller-Hinton agar. Filter paper discs were impregnated with the obtained extracts in order to determine the bacterial activity. Assays performed in triplicate. A halo of inhibition was observed only in discs containing oxacillin. The literature review showed the broad potential of extracts from parts of Moringa oleifera against different microorganisms. Such activity, however, was not observed in this experiment, which highlights the importance of further studies about the characteristics of the plant.